The canceling of the American mind : cancel culture undermines trust, destroys institutions, and threatens us all--but there is a solution, - Lukianoff, Greg; Schlott, Rikki (Simon and Schuster, 2023)
"A timely deep dive into cancel culture, an account of its dangers to all Americans, and the much-needed antidote from the team that brought you Coddling of the American Mind. Cancel culture is a new phenomenon, and The Canceling of the American Mind is the first book to codify it and survey its effects. From the team that brought you the bestselling Coddling of the American Mind comes hard data and research on what cancel culture is and how it works, along with hundreds of new examples showing the left and the right both working to silence their enemies. The Canceling of the American Mind will change how you view cancel culture. Rather than a moral panic, we should consider it a dysfunctional part of how Americans battle for power, status, and dominance. Cancel culture is just one symptom of a much larger problem: the use of cheap rhetorical tactics to "win" arguments without actually winning arguments. After all, why bother refuting your opponents when you can just take away their platform or career? The good news is that we can beat back this threat to democracy through better citizenship. The Canceling of the American Mind offers concrete steps toward reclaiming a free speech culture, with materials specifically tailored for parents, teachers, business leaders, and everyone who uses social media. We can all show intellectual humility and promote the essential American principles of individuality, resilience, and open mindedness"--